2021
DOI: 10.1038/s41375-021-01136-1
|View full text |Cite
|
Sign up to set email alerts
|

EOMES and IL-10 regulate antitumor activity of T regulatory type 1 CD4+ T cells in chronic lymphocytic leukemia

Abstract: The transcription factor eomesodermin (EOMES) promotes interleukin (IL)-10 expression in CD4+ T cells, which has been linked to immunosuppressive and cytotoxic activities. We detected cytotoxic, programmed cell death protein-1 (PD-1) and EOMES co-expressing CD4+ T cells in lymph nodes (LNs) of patients with chronic lymphocytic leukemia (CLL) or diffuse large B-cell lymphoma. Transcriptome and flow cytometry analyses revealed that EOMES does not only drive IL-10 expression, but rather controls a unique transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…Eomes was shown to promote Tr1 development by promoting IL-10 production and preventing the development of other subsets in concert with B Blimp-1 in a mouse model of allogenic bone marrow transplantation [ 53 ]. Similar observations were made in a murine leukemia model, in which Eomes expression by CD4 T cells was shown to be critical for generating Tr1 cells that also exhibited cytotoxic function [ 54 ]. Together, with the results above focused on Foxp3 + Tregs, these results indicate that expression of Eomes by CD4 T cells may either positively or negatively impact suppressive modulation of ongoing immune responses depending on the predominating regulatory CD4 T cell subset.…”
Section: Eomes In Regulatory Cd4 T Cellssupporting
confidence: 69%
See 1 more Smart Citation
“…Eomes was shown to promote Tr1 development by promoting IL-10 production and preventing the development of other subsets in concert with B Blimp-1 in a mouse model of allogenic bone marrow transplantation [ 53 ]. Similar observations were made in a murine leukemia model, in which Eomes expression by CD4 T cells was shown to be critical for generating Tr1 cells that also exhibited cytotoxic function [ 54 ]. Together, with the results above focused on Foxp3 + Tregs, these results indicate that expression of Eomes by CD4 T cells may either positively or negatively impact suppressive modulation of ongoing immune responses depending on the predominating regulatory CD4 T cell subset.…”
Section: Eomes In Regulatory Cd4 T Cellssupporting
confidence: 69%
“…Eomes may promote protective CD4 T cell activity by directly binding the regulatory regions of inhibitory molecules, thus lowering their expression on effector cells and increasing their effectiveness at tumor sites [ 117 ]. Conversely, Eomes + Tr1 cells expressing cytolytic markers and PD-1 have been found in patients with chronic lymphocytic leukemia (CLL) [ 54 ]. While the role of these cells in CLL patients is unclear, studies using mouse models show that Tr1 cells can control tumor growth through IL-10 production and Eomes-mediated cytolytic activity [ 54 ].…”
Section: Eomes In Cancer Immunitymentioning
confidence: 99%
“…Tr1 cells produce IL-10 and express coinhibitory receptors, but also harbor cytotoxic activity ( 100 ). A single study thus far has investigated Tr1-like cells in CLL and lymphoma ( 101 ). The authors observed accumulation of Tr1-like cells in CLL and DLBCL patients’ lymph nodes compared to reactive lymph node controls.…”
Section: T Regulatory Type 1 Cellsmentioning
confidence: 99%
“…In the transgenic and adoptive transfer Eμ-TCL1 mouse models of CLL, Tr1-like cells were found to be essential for CD4 + T cell-mediated control of leukemia development. Further, the study showed that IL-10 signaling was important for the cytotoxic capabilities of these cells ( 101 ). As Tr1 cells share phenotypic and functional similarities with both conventional Tregs and effector Tregs, further studies will be essential to define characteristics of this enigmatic subset in the context of lymphoid malignancies.…”
Section: T Regulatory Type 1 Cellsmentioning
confidence: 99%
“…AHR and IRF4 contribute to the suppressive capacity of Tr1 cells ( 37 ), but the involvement of these transcription factors in human Tr1 differentiation remains unknown. Eomes is the only transcription factor that has been demonstrated to play a role in the differentiation of a subset of human Tr1 cells ( 11 , 38 , 39 ). However, bulk RNA sequencing revealed that Eomes was not differentially expressed in circulating Tr1 cells compared to non-Tr1 memory CD4 + T cells ( 26 ), so it is unlikely to be a lineage-defining transcription factor for all Tr1 cells, and instead may only identify a subset of Tr1 cells.…”
Section: Classification Of Tr1 Cells and Mechanisms Of Their Inductionmentioning
confidence: 99%